Legal Issues in Converting Wildlife Sanctuaries into Palm Oil Plantations - Diki Okta Dwi Putra; Simarmarta, Anggi Sri Haryati; Maulana, M. Ramzi (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2026)
The sustainability of wildlife reserve forests is threatened by deforestation activities into non-forest areas, especially into oil palm plantations. Currently, Indonesia is the largest palm oil producer in the world with the latest production figures recorded at 37.8 million tons and it contributes foreign exchange of 310 trillion rupiah from exports, which are predicted to continue to increase in number every year. this raises legal issues related to how the regulation of deforestation in Indonesia that changes the function of forests into oil palm plantations is reviewed from the legislation and how the company's liability for damage to Wildlife Sanctuary Parks due to deforestation of forests into oil palm plantations according to the results of the law The legal rules regarding deforestation are quite clear as in the Government Regulation on the Implementation of Forestry No. 23 of 2021, but the regulations regarding the licensing of oil palm land clearing are still not specifically regulated, so that the Transfer of forest clearing licenses is still not regulated. 23 of 2021, but regulations regarding the licensing of oil palm land clearing are still not specifically regulated, so that the conversion of the Wildlife Reserve forest functions into oil palm plantations is a form of forest deforestation, which is not allowed at all to be deforested as oil palm plantations.